Changes in platelet-rich fibrin composition after trauma and surgical intervention. (16th November 2020) - Verboket, René D.; Anbar, Bechir; Söhling, Nicolas; Kontradowitz, Kerstin; Marzi, Ingo; Ghanaati, Shahram; Henrich, Dirk
Abstract: Reconstruction surgery after trauma has always been a big challenge. The use of platelet-rich fibrin (PRF) as an autologous source could help accelerate the regeneration time of bone and soft tissues. PRF is a blood concentrate system obtained through a one-step centrifugation. The 3D matrix of the PRF clot serves as a reservoir of growth factors. In the present study, PRF from patients after trauma and after surgery was compared to healthy volunteers to evaluate the composition and potential of PRF as a possible autologous tool for growth factor delivering. Two PRF species and blood from healthy volunteers and patients after trauma and after following surgical intervention were compared (n = 10). FACS analysis, ELISA, and histological analysis were performed. The Pro-inflammatory potential after trauma and after the intervention is increased in PRF species whereas cellular and humoral factors with distinct regenerative potential remained on a level comparable to peripheral blood. It was demonstrated that cells in PRF express more pro-inflammatory species when obtained after the surgical intervention compared to PRF from healthy individuals. This pro-inflammatory potential should be considered, when combining PRF with bone substitute materials for reconstruction surgery prone to foreign body giant cell reaction. Accordingly, solid or injectable PRF-based matrices should preferably be prepared prior to a surgical intervention.